Internet, Identity and Islamic Movements: The Case of Salafism in Indonesia - Asep M. Iqbal (Islamika Indonesiana, 2014)
The revolution of information and communication technology has transformed the world into different shape, including Muslim world. This technology in the form of internet does not merely have the democratizing potential for Muslim world, but also has created a new public sphere and new Islamic authority. This paper discusses the role of internet as played by Muslim religious movement, especially Salafism in Indonesia. Using textual analysis of data collected from their websites, this article argues that the internet as modern technology of information and communication has helped Salafism rise to the public to show their ideological and doctrinal stances as well as to challenge their enemies such as Liberal Islam Network (Jaringan Islam Liberat), Shiah, and so on. Through the internet too, this movement respond to such contemporary issues as terrorism, earthquake and others. This means that although orthodox in doctrine and attitude, this movement can benefit from the internet very much for its missionary purposes.